Collaborative participatory research as a learning process: the case of CIP and CARE in Peru - Ortíz, Oscar; Frias, Guillermo; Ho, Raul; Cisneros, Hector; Nelson, Rebecca; Castillo, Renee; Orrego, Ricardo; Pradel, W.; Alcázar, Jesus; Bazan, Mario (International Maize and Wheat Improvement Center, 2005)
Participatory research (PR) has been analyzed and documented from different points of view, but particularly taking into consideration the benefits that this process generates for farmers. Studies of the benefits of PR for other actors such as field staff, researchers and organizations have been limited, with organizational learning receiving the least attention. This paper analyzes the interaction between the International Potato Center (CIP) and CARE in Peru and makes the case that PR can also contribute to creating a collaborative learning environment that generates important lessons for the individuals and organizations involved. The paper describes the evolution of the collaborative environment of these two institutions for more than a decade. Three interactive learning periods are presented, namely the “information transfer period” (1993 –1996) the “action-learning period” (1997-2002), and the “social learning period” (on-going). Several lessons from each period, as well as changes in institutional contexts and perceptions, are described. The CIP-CARE case shows that research and developmentoriented organizations can interact fruitfully using PR as a mechanism to promote learning, as well as flexibility in interaction and innovativeness, and that a process of osmosis of information occurs between groups that use PR in a specific case to other groups within the organizations, influencing behavior. However, the paper also indicates that institutional learning should be promoted more specifically in order to extract guidelines from the lessons, which can influence the way organizations plan and implement their projects in a constantly changing environment.